Morphology of the midgut of Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) adult ticks in different feeding stages - Remedio, R. N. [UNESP]; Sampieri, B. R. [UNESP]; Vendramini, M. C R [UNESP]; Souza, N. M. [UNESP]; Anholeto, L. A. [UNESP]; Denardo, T. A G B [UNESP]; Camargo-Mathias, M. I. [UNESP] (Springer Nature, 2013)
The intestinal epithelial cells of ticks are fundamental for their full feeding and reproductive success, besides being considered important sites for the development of pathogens. Rhipicephalus sanguineus ticks are known for their great medical and veterinary importance, and for this reason, the knowledge of their intestinal morphology may provide relevant subsidies for the control of these animals, either by direct acaricidal action over these cells or by the production of vaccines. Therefore, this study aimed to describe the midgut morphology of male and female R. sanguineus ticks in different feeding stages, by means of histological analysis. Significant differences were observed between the genders, and such alterations may refer mainly to the distinct demands for nutrients, much higher in females, which need to develop and carry out the egg-laying process. In general, the midgut is coated by a thin muscle layer and presents a pseudostratified epithelium, in which two basic types of cells can be observed, connected to a basal membrane - generative or stem and digestive cells. The latter was classified as follows: residual, deriving from the phase anterior to ecdysis; pinocytic, with vesicles containing liquid or pre-digested components of blood; phagocytic, with entire cells or remnants of nuclear material inside cytoplasmic vesicles; and mature, free in the lumen. Digestion is presumably intracellular and asynchronous and corresponds to a process which starts with the differentiation of generative cells into pinocytic digestive cells, which subsequently start to phagocytize intact blood cells and finally detach from the epithelium, being eliminated with feces. © 2012 Springer-Verlag Berlin Heidelberg.
Keywords: adult animal; basement membrane; blood analysis; controlled study; digestive system examination; egg laying; feeding behavior; female; histology; male; microbial morphology; midgut; molting; nonhuman; parasite transmission; phagocytosis; pinocytosis; priority journal; Rhipicephalus sanguineus; sex difference; Animals; Feeding Behavior; Female; Gastrointestinal Tract; Histocytochemistry; Male; Microscopy; Sex Factors; Acari; Animalia; Ixodida; Ixodidae